Retorik, hegemoni och musikforskning:: Mot en pragmatisk syn på musikvetenskapen - Pontara, Tobias (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2008)
The proliferating production during the last decades of articles and books concerned with the discipline of musicology itself has, for better or worse, led to the construction of the topic as a noticeable research area of its own within musicology. While it is certainly true that British and American scholars have been responsible for the major part of the output in this area, discussions have by no means been absent in other countries. The present article considers three suggestions offered by Swedish musicologists as to how musicology as a discipline should be understood. I argue that though very different, or even incompatible, in their varying conceptions of the discipline, they nevertheless share a common weakness in that they all suffer from too a narrow a view of what it is musicology should be doing. The second part of the article then develops a different approach to the issue, arguing that musicology should be seen as a cluster of overlapping language games rather than a fixed and stable entity defined by specific methods and perspectives.